ASPECTS OF ASSET VALUATIONS. - Paton, William A. (The Accounting Review, 1934)
Abstract The author of the article assumes that revaluation of a cost-of-replacement basis is in general quite as defensible as revaluation on a value-of-money basis and has, at bottom much the same line of justification. From a balance-sheet standpoint, there is not much to be said for revaluation on a cost-of-replacement basis of plant assets particularly specialized depreciable assets, even in a period of rapidly changing prices. The author states that balance sheet figures cannot be expected to show realizable values in the case of plant assets and as expressions of cost incurred. It is hard to see any advantage in current estimated costs over actual dollar costs for balance-sheet purposes. In fact a footnote or a careful reference to the changing situation is as valuable as the adjusted figures themselves. On the other hand, there is hardly any serious objection to the introduction of careful estimates of replacement costs in the balance sheet provided it is done, as is almost never the case, in a proper manner, and this should mean, among other things, that the extent of the adjustment is clearly displayed.